Loveless eaudiobook - Oseman, Alice (Scholastic Audio Books, 2022)
For fans of Love, Simon and I Wish You All the Best, a funny, honest, messy, completely relatable story of a girl who realizes thatlove can be found in many ways that don't involve sex or romance. From the marvelous author of Heartstopper comes an exceptional YA novel about discovering that it's okay if you don't havesexual or romantic feelings for anyone . . . since there are plenty of other ways to find love and connection.This is the funny, honest, messy, completely relatable story of Georgia, who doesn't understand why she can't crush and kissand make out like her friends do. She's surrounded by the narrative that dating + sex = love. It's not until she gets to collegethat she discovers the A range of the LGBTQIA+ spectrum — coming to understand herself as asexual/aromantic. Disrupting thenarrative that she's been told since birth isn't easy — there are many mistakes along the way to inviting people into a newly foundarticulation of an always-known part of your identity. But Georgia's determined to get her life right, with the help of (and despite themajor drama of) her friends.